Putting the Earth into Science: Resource, Workshop and Field Trip for High School Science Teachers at GeoCanada 2010 - Heenan, Stella; Nowlan, Godfrey; Clinton, Laura (Geoscience Canada, 2011)
SUMMARY Putting the Earth into Science is a classroom resource that takes an interdisciplinary approach to expanding Earth science content in Canadian high schools. In recent history, Earth science has struggled to be identified as a core subject in school curricula. Differing approaches of whether it is placed in social studies (geography) or science has resulted in identity confusion. Alternatively, it is often seen as a specialist area of study, and hence optional. As a solution to this problem, the National EdGEO Workshop Program has developed a series of curricula-based lesson plans to integrate Earth science topics into the core subjects of physics, chemistry, biology and mathematics. The program will attract teachers of diverse science disciplines, and deliver a meaningful educational experience and important career information to high school students who are largely unaware of how Earth science impacts their daily lives. Putting the Earth into Science was launched during a workshop and field trip offered to teachers across Canada in conjunction with GeoCanada 2010.